Pemasangan Lampu Jalan Tenaga Surya Di Kampung Benda Desa Mekarjaya, Panongan - Tangerang - Taryana; Suprihartini, Yayuk; Soebiantoro, Rubby; samanhudi, Asep (Politeknik Penerbangan Indonesia Curug, 2021)
The road is an important access for residents to do activities, but if the road is not equipped with lighting it will become an obstacle, especially at night. Street lighting is something that is really needed by residents, especially in rural areas. Street lighting is a tool that is needed by residents in Kp. Blok Benda RT.10 RW. 04 Desa Mekar Jaya Kec. Panongan Tangerang Banten. Therefore, the people of Kp. Blok Benda Mekar Jaya want the procurement and installation of street lighting to be carried out immediately along the roads belonging to the Panongan area, especially roads that are considered prone to criminal acts / theft Seeing the demand for residents who really need street lighting, we implemented the Tri Darma Perguruan Tinggi where the Indonesian Aviation Polytechnic Curug is one of the lecturers' obligations in carrying out community service by taking cases